2002
DOI: 10.7164/antibiotics.55.571
|View full text |Cite
|
Sign up to set email alerts
|

Arylomycins A and B, New Biaryl-bridged Lipopeptide Antibiotics Produced by Streptomyces sp. Tue 6075. II. Structure Elucidation.

Abstract: The structures of new lipopeptide antibiotics, arylomycins A and B, were elucidated by a combination of ESI-FTICR-mass spectrometry, NMR spectroscopy, EDMAN sequencing, and fatty acid and chiral amino acid analyses. The colourless arylomycins A share the peptide [3,3]biaryl bond between MeHpg5 and Tyr7. The yellow arylomycins B differ from arylomycins A by nitro substitution of Tyr7. The N-termini of arylomycins A and B are acylated with saturated C11-C15 fatty acids (fa1) comprising n, iso, and anteiso isomer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
65
0
11

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(79 citation statements)
references
References 1 publication
3
65
0
11
Order By: Relevance
“…At the time of the completion of this work, a literature search revealed that this family of lipoglycopeptides is novel. Subsequently, we learned that structures of a similar family of lipopeptides, called arylomycins, have been disclosed in a conference proceeding (35) followed by a publication (36). The major structural difference is the absence of the sugar unit in arylomycins.…”
Section: Resultsmentioning
confidence: 99%
“…At the time of the completion of this work, a literature search revealed that this family of lipoglycopeptides is novel. Subsequently, we learned that structures of a similar family of lipopeptides, called arylomycins, have been disclosed in a conference proceeding (35) followed by a publication (36). The major structural difference is the absence of the sugar unit in arylomycins.…”
Section: Resultsmentioning
confidence: 99%
“…1) (11)(12)(13). Despite the essentiality, conservation, and relative accessibility of SPase (10,14), the arylomycins were initially reported to have a narrow spectrum of activity (12,13).…”
mentioning
confidence: 99%
“…The arylomycins are a class of natural product antibiotics isolated in 2002 and subsequently shown to inhibit Escherichia coli SPase in vitro (41,95). We have synthesized a variety of arylomycins, including the derivative arylomycin A-C 16 ( Fig.…”
mentioning
confidence: 99%